Design and development of thermodynamics apparatus using design for manufacture and assembly (DFMA) methodology - Wan Ibrahim, Wan Abd. Rahman Assyahid (2006)
Thermodynamics is an essential subject in Mechanical Engineering curriculum. The thermodynamics principles have been applied in many applications to fulfill human needs. Mechanical engineers use thermodynamics principles in their study to design a wide variety of energy system such as jet engines and rockets, refrigeration system, air conditioning system, chemical process and power plant. This would explain that thermodynamic was one of the critical areas which need to be well understood. However, the majority of students perceive thermodynamics as a difficult subject. By having the suitable experiment apparatus designed to demonstrate thermodynamics process and system have been learned, such an apparatus would enhance the teaching and learning of thermodynamics. Therefore, an apparatus for this purpose is necessary to be developed. The apparatus should be portable and mobilize which demonstration in both lecture and laboratory session is possible. A Boothroyd-Dewhurst Design for Manufacturing and Assembly (DFMA) Methodology had been applied to optimize the design apparatus. The application of Boothroyd-Dewhurst (DFMA) Methodology will simplify the design through minimizing the part component for ease of assembly and manufacture. In addition, this methodology also provides analysis for selection of manufacturing process and material for developed apparatus. Therefore, the overall development cost could be minimized. The aim of this project is to successful develop an apparatus which could demonstrate the 1st Law of Thermodynamics-closed system based on Boothroyd-Dewhurst DFMA Methodology.